Academic Resilience and Preparedness of Alternative Learning System (ALS) Students for Tertiary Education - Tabanao, Eden Grace (Journal of Interdisciplinary Perspectives, 2025)
This study explored the academic resilience and college preparedness of senior high school students in the Alternative Learning System (ALS) to understand their transition challenges to tertiary education. Despite the growing importance of ALS as a second-chance education program, limited research has explored how resilient and prepared these learners are for tertiary education. The study employed a descriptive research design using total population sampling. All 29 ALS Senior High School students were included as participants, as they represented the entire enrolled population during the study. Data were gathered through a validated survey questionnaire measuring demographic profile, academic resilience, and preparedness, and analyzed using descriptive statistics, including frequencies, percentages, and weighted means. Results show that most learners are non-traditional students: 83% are aged 21–40, predominantly female (90%), and from low-income families (55% earn less than ₱5,000 monthly). Many aspire to pursue tertiary education, particularly in Education (41%) and Criminology (24%). Findings further indicate a moderate to high level of academic resilience (overall mean = 3.68), with strengths in confidence, intuition, and emotional regulation, but weaknesses in crisis management and conflict resolution. Similarly, learners reported a moderate level of preparedness for college (overall mean = 3.51), demonstrating readiness in course selection, computer literacy, and social interaction, but uncertainty in academic skills, study habits, financial readiness, and admission requirements. The study concludes that ALS provides learners with essential resilience and soft skills but requires strengthened support in academic bridging, financial assistance, and socio-emotional development. These findings underscore the importance of enhancing ALS pedagogy, guidance services, and institutional linkages to facilitate smoother transitions to tertiary education for marginalized learners.